DEPRESI SILANG DALAM BIJI DAN SEMAI Melaleuca alternifolia - Liliana Baskorowati (Center for Forest Biotechnology and Tree Improvement (CFBTI), 2017)
Tea tree (Melaleuca alternifolia) is known as an essential oil producer. This species is commercially important as a source of essential oil especially in Australia. To improve its oil quality, research on artificial pollination between plus trees were carried out. The information about self-incompatibility and inbreeding depression due to self-pollination should be ascertained to support the pollination success. This study was aimed at examining the self-incompatibility of tea tree by conducting controlled self-pollination and cross-pollination. Controlled cross and self-pollination were carried out at a seedling seed orchard of tea tree, using four mother trees as experimental samples. Natural self-pollination was undertaken by bagging nopened flowers, without emasculation and counting the number of capsule set. Open pollination was used as a control treatment, of which the number of unopened flowers and the number of capsule set were counted. Observations revealed that no capsule was found from controlled self pollination (with the index self-incompatibility = 0), even though natural self-pollination produced low number of capsules (with the index self-incompatibility = 0.24). Therefore, it can be assumed that high level of self-incompatibility was took place in tea tree. Inbreeding depression also existed in this species, revealed by the decreased number of capsul set, lower seed germination rate of self-pollinated seeds than cross pollinated seeds. The slower growth of self-pollinated seedlings than cross pollinated seedlings in the nursery also indicated that inbreeding depression occured.